Prophecy, Interpretation, and Social Criticism - Ellen F. Davis; Sarah Musser (St Andrews Encyclopaedia of Theology, 2023)
Prophetic figures and words are evoked throughout the Old and the New Testaments, from Genesis to Revelation, and they are a foundational resource for liturgy and theology in both Jewish and Christian traditions. The prophets’ most important role, performed in the public eye and sometimes in the presence of kings, is to interpret their own culture and historical moment from the perspective of the divine. Very often these prophetic acts of interpretation issue in social criticism, as prophets proclaim God’s judgment against king and/or people. This article does not attempt to provide a full overview of the phenomenon of prophecy in the Hebrew Bible/Old Testament. Rather, after a brief overview of the prophetic literature and role, it focuses on the complex relationships between prophecy, interpretation, and social criticism. This article looks at various aspects of prophetic texts in both Former and Latter Prophets, first in the context of the social structures and agrarian economy of ancient Israel, and secondarily with concern for how those ancient texts may speak to contemporary social situations around the globe. These narratives and poetic oracles of doom and hope put in prophetic perspective the complex ways that religious leaders may interact with those who hold, and often abuse, political and economic power. The prophetic books are to a great extent trauma literature, reflecting the harsh realities of war and exile, unjust land appropriation, famine, and devastating drought. The prophetic message may speak most directly to the current historical moment as it highlights the God-given integrity and flourishing of the created order and how that integrity is disrupted through human misconduct. Although the Prophets are unsparing in their exposure of sin, the whole prophetic canon is editorially shaped to point toward hope for the restoration of Israel and Judah, with the royal house of David as a focal point of radical hope.